Development of Ternary and Quaternary Catalysts for the Electrooxidation of Glycerol - L. M. Artem; D. M. Santos; A. R. De Andrade; K. B. Kokoh; J. Ribeiro (The Scientific World Journal)
This work consisted in the preparation of platinum-based catalysts supported on carbon (Vulcan XC-72) and investigation of their physicochemical and electrochemical properties. Catalysts of the C/Pt-Ni-Sn-Me (Me = Ru or Ir) type were prepared by the Pechini method at temperature of 350∘C. Four different compositions were homemade: C/Pt60Sn10Ni30, C/Pt60Sn10Ni20Ru10, C/Pt60Sn10Ni10Ru20, and C/Pt60Sn10Ni10Ir20. These catalysts were electrochemically and physically characterized by cyclic voltammetry (CV), chronoamperometry (CA) in the presence of glycerol 1.0 mol dm-3, X-ray diffraction (XRD), and high-resolution transmission electron microscopy (HRTEM). XRD results showed the main peaks of face-centered cubic Pt. The particle sizes obtained from XRD and HRTEM experiments were close to values ranging from 3 to 8.5 nm. The CV results indicate behavior typical of Pt-based catalysts in acid medium. The CV and CA data reveal that quaternary catalysts present the highest current density for the electrooxidation of glycerol.